2020
DOI: 10.1002/mgg3.1274
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Variants identified in FBN1 and TGFBR2 in seven Iranian families with suspected Marfan syndrome

Abstract: Background Marfan syndrome (MFS) is a multi‐systemic autosomal dominant disease of the connective tissue characterized by the early development of thoracic aneurysms/dissections, along with various manifestations of the ocular and skeletal systems. Due to the genetic and clinical heterogeneity, the clinical diagnosis of this disorder is challenging. Loss‐of‐function mutations in FBN1 (encodes fibrillin‐1) lead to MFS type 1. Also, similar mutations in transforming growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…TGF‐β needs the SMAD family to function normally, and it stimulates a variety of physiological processes such as tissue repair, cell growth, cell differentiation and cell proliferation. 60 , 61 TGF‐β activates two types of receptors including the activin receptor‐like kinase 1 (ALK1) and ALK5. TGF‐β stimulates (using ALK1) or inhibits (via ALK5) the migration and proliferation of endothelial cells.…”
Section: Smad4 Functions Through Different Signalling Pathwaysmentioning
confidence: 99%
“…TGF‐β needs the SMAD family to function normally, and it stimulates a variety of physiological processes such as tissue repair, cell growth, cell differentiation and cell proliferation. 60 , 61 TGF‐β activates two types of receptors including the activin receptor‐like kinase 1 (ALK1) and ALK5. TGF‐β stimulates (using ALK1) or inhibits (via ALK5) the migration and proliferation of endothelial cells.…”
Section: Smad4 Functions Through Different Signalling Pathwaysmentioning
confidence: 99%
“…Identification of FBN1 variants by WES substantiates the potential of NGS technologies. Several other studies have also identified genetic variants in FBN1 and FBN2 independently in different populations 21-24 . Fibrillin-1 is a structural macromolecule that polymerizes into microfibrils; multiple mouse models have shown the functional importance of FBN1 gene variants 25 .…”
Section: Scoliosismentioning
confidence: 93%